1992
DOI: 10.5032/jae.1992.01046
|View full text |Cite
|
Sign up to set email alerts
|

Learning Styles, Teaching Styles And Personality Styles Of Preservice Teachers Of Agricultural Education

Abstract: Each teacher is unique in many ways. Teachers vary from one another in such characteristics as learning style, teaching style and personality style. Research has been conducted in several teacher education disciplines with regard to the selected teacher characteristics of learning style (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 4 publications
8
28
0
2
Order By: Relevance
“…Additionally, it was found that demographics including the work years, the highest degree held, owning or operating a farm, and the organizations involvement could influence teachers' attitude toward the selected science and technology topics to some extent. This results consistent with some literatures, which suggest that demographics play a role in helping determine an individual's attitudes and practice (Schommer, 1998;Cano et al, 1992).…”
Section: Implications and Significance To High School Agricultural Edsupporting
confidence: 92%
“…Additionally, it was found that demographics including the work years, the highest degree held, owning or operating a farm, and the organizations involvement could influence teachers' attitude toward the selected science and technology topics to some extent. This results consistent with some literatures, which suggest that demographics play a role in helping determine an individual's attitudes and practice (Schommer, 1998;Cano et al, 1992).…”
Section: Implications and Significance To High School Agricultural Edsupporting
confidence: 92%
“…Several studies (Cano et al, 1992;Raven, et al, 1993;Torres and Cano, 1994;Cano and Metzger, 1995;Miller, 1995;Whittington and Raven, 1995) have been conducted with the primary aim of describing the learning styles of a particular population of agricultural learners. Most of these studies imply that knowledge of learning styles may be used by teachers to improve instruction.…”
Section: Resultsmentioning
confidence: 99%
“…Student-centered learning has been pushed in the agricultural education area [61,102]. Research found 60% of sampled agriculture teachers were inclined to use student-centered learning [103]. Hess and Gong [104] believed student-centered learning is a path to college and career readiness.…”
Section: Discussionmentioning
confidence: 99%